Decline of Empathy among Healthcare Apprentices - Mohammed O. Razi; Rinat Fouzia; Mohammed S. Razzaque (International Medical Education, 2023)
Empathy is a crucial human quality that enables healthcare professionals to connect with patients, providing physical and emotional support to enhance patient-centered care. Empathy in healthcare is critical for establishing patient-provider (healthcare) trust, increasing patient satisfaction, and, eventually, delivering high-quality healthcare. However, there is growing concern about the declining levels of empathy among healthcare providers, partly related to increased workload, burnout, and empathic distress fatigue. Moreover, the recent emphasis of medical education on the technical aspects of healthcare over empathetic care also contributed to the decline of empathy among healthcare providers with compromised patient care. This brief article summarizes the potential causes and consequences of declining empathy in medical practice with future implications on the quality of humanized healthcare.